Analysis of Islamic Messages on the Instagram Account @quranreview Using the Philipp Mayring Model Approach - Andhika Wahyu Permadi; Fiona Niska Dinda Nadia; Yudistira Ardi Nugraha Setyawan Putra (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study aims to systematically analyze the categories of Islamic messages conveyed by @quranreview Instagram account during August 2025, using a qualitative content analysis approach according to Philipp Mayring. This research uses a descriptive qualitative approach, The data period consists of uploaded documentation (feeds, reels, and carousels) throughout August 2025. The analysis was carried out following Mayring's procedure: determining the unit of analysis, forming deductive and inductive categories, coding, and thematic interpretation. The novelty of this study is that data collection covering August 2025 provides the most up-to-date insights into the trends of da'wah messages on @quranreview. In addition, the application of Philipp Mayring's content analysis model provides validity and a more rigorous analytical framework than previous studies that were only descriptive. The results of the study show that three main categories emerged consistently—aqidah (belief), sharia (practice of worship), and akhlak (ethics). Engaging and contextual visual presentation. Content that incorporates elements of lighthearted humor or trending themes—for example, “mindfulness in worship”—showed the highest levels of interaction (likes, comments, and reposts), demonstrating the effectiveness of contextual digital da'wah. Patterns emerged in the messages that connect traditional Islamic values ​​with the daily experiences of the younger generation, creating a bridge between the textuality of the Quran and the dynamics of modern life.